Soft Skills in Engineering Education: From the Macro Curriculum to International Standards - Álvarez, Johny A.; Herrera, Andrés; Yepes, Sara M.; Montes, Willer F.; Ardila, Juan G. (Journal of Engineering Education Transformations, 2025)
Soft skills are increasingly important in the current context of engineering education because disciplinary learning is now greatly facilitated by technology, and students (on their own) have access to an almost infinite amount of information and knowledge. To acquire these skills, engineering students need to work on their emotions, ethics, and other personal areas. This article analyzes the case of the Instituto Tecnológico Metropolitano (ITM) in Medellín, Colombia, more specifically, its Faculty of Engineering, whose educational project acknowledges that it has a shortcoming in terms of teaching soft skills. Therefore, document analysis was carried out using the documents that compose ITM’s macro curriculum to identify the soft skills that this Higher Education Institution (HEI) proposes for its engineering students and graduates—all of them were compared to the competencies suggested by international associations. This study combined two methodologies, i.e., conceptual cartography and document analysis (for collecting information) and explored the skills that the labor market is currently demanding from engineering graduates. As a result, it was possible to link the generic skills in ITM’s engineering macro curriculum with the generic competencies currently needed by professionals in different engineering fields. It was found that said macro curriculum meets current educational standards in this regard. Nevertheless, the ITM still suffers from gaps in terms of (1) ensuring that professors and directors comply with what is established in its institutional documents and (2) identifying the parts of the educational chain that can destabilize its institutional plan.